The normal and pathological language - Espejo, Luis D. (1920)
The machine language is extraordinarily complex. Since the discovery of the motor center of the floor for the BROCA in 1861 to recent research by PIERRE MARIE, has accumulated a huge number of anatomical and clinical observations, it has been subject to various interpretations. While some authors undisputed reputation affirm the real existence of specific centers for the different language modalities. others flatly deny the existence of special schools and consider language as the product of the integral activity of the brain. However, there is no denying the undeniable importance of certain districts and other lower brain centers play in the mechanism of this function.